Novel alternative ribonucleotide excision repair pathways in human cells by DDX3X and specialized DNA polymerases. Issue 20 (2nd November 2020) - Riva, Valentina; Garbelli, Anna; Casiraghi, Federica; Arena, Francesca; Trivisani, Claudia Immacolata; Gagliardi, Assunta; Bini, Luca; Schroeder, Martina; Maffia, Antonio; Sabbioneda, Simone; Maga, Giovanni
Abstract: Removal of ribonucleotides (rNMPs) incorporated into the genome by the ribonucleotide excision repair (RER) is essential to avoid genetic instability. In eukaryotes, the RNaseH2 is the only known enzyme able to incise 5′ of the rNMP, starting the RER process, which is subsequently carried out by replicative DNA polymerases (Pols) δ or ϵ, together with Flap endonuclease 1 (Fen-1) and DNA ligase 1. Here, we show that the DEAD-box RNA helicase DDX3X has RNaseH2-like activity and can support fully reconstituted in vitro RER reactions, not only with Pol δ but also with the repair Pols β and λ. Silencing of DDX3X causes accumulation of rNMPs in the cellular genome. These results support the existence of alternative RER pathways conferring high flexibility to human cells in responding to the threat posed by rNMPs incorporation.